Penerapan Model Pembelajaran Student Teams Achievement Divisions (STAD) dalam Meningkatkan Hasil Belajar IPA Peserta Didik SMP - Andi Rofina; Andi Rugaiyah (Madrasah Tsanawiyah DDI Cilellang, 2020)
This study aims to analyze efforts to improve science learning outcomes of mechanical energy materials through cooperative learning of Student Team Achievement Division (STAD) model in class VIII students of SMP Negeri 2 Liliriaja, Soppeng Regency. This research is a classroom action research using a qualitative approach, the researcher acts as a teacher who works to collect and analyze data. The results showed that the cooperative learning of STAD model in learning science of mechanical energy material was carried out through seven stages, namely preparation of learning, presentation of material, study in groups, examination of group learning outcomes, working on individual tests, examination tests, and group awards. In the first learning cycle, learning completeness criteria do not meet the performance indicators. After going through the second learning cycle, students are more active in learning participation, students are more enthusiastic in group discussions and class discussions, student understanding increases in answering tests verbally and in writing, increase student responses to learning, and also increases learning achievement. Because learning objectives have been achieved, the learning is considered successful and it was concluded that the cooperative learning of Student Team Achievement Division (STAD) model can improve students' science learning outcomes in class VIII of SMP Negeri 2 Liliriaja, Soppeng Regency